The Influence of Social Networks on the Livelihoods of Urban Refugees in Dar es Salaam, Tanzania - Daniel Namkesa, Faraja (Tanzania Journal for Population studies and Development, 2024)
This study examined the influence of social networks in enhancing the livelihoods of urban refugees in Dar es Salaam City, Tanzania. It focused on the key actors within the social networks of urban refugees, as well as the effectiveness of these networks on enhancing the livelihoods of refugees in Dar es Salaam City. Social network and actor network theories guided this study. Using a qualitative approach, data was collected through focus group discussions and document reviews. Four focus groups were organized, involving Burundian men, Congolese men, Congolese women, and a mixed group of Congolese and Burundian youth. Thematic analysis was employed to identify key themes and patterns in the data. Findings revealed that urban refugees rely on various social networks, both formal and informal, ranging from government to non-government organizations, international organizations, families, and friends. Actors in the formal networks included Dignity Kwanza, Tanganyika Christian Refugee Services (TCRS), Relief to Development Society (REDESO), Church World Services (CWS), UNHCR, and the Refugee Department under the Ministry of Home Affairs, which provides training, financial, and legal support. In addition, informal networks that refugees have established include family and friendship within the host community, offering critical moral, social, and material support. The results suggest that, while formal network support in the form of training has not significantly improved the livelihoods of refugees due to policy restrictions, informal networks, specifically those made up of family and friendship ties, were effective in enhancing the livelihoods of these refugees in Dar es Salaam. The study recommends tailoring training initiatives for refugees within Tanzania’s refugee policy context, to optimize their impact on their livelihoods.